ETHANOL EXTRACTS OF TUBERS DIOSCOREA ALATA L. AS NTIALLERGIC AGENT ON MICE BALB/C INDUCED WITH OVALBUMIN - SRI NABAWIYATI NURUL MAKIYAH; ZULKHAH NOOR; WIDODO; MUHAIMIN RIFA’I; MOCH. SASMITO DJATI (International Journal of Pharma and Bio Sciences, 2014)
This study aimed to analyse the effects of ethanol extract tuber Dioscorea alata L. (EEDA) on mice induced by Ovalbumin using the measurement of IgE, IL-4 and TNF-a level. The experimental research on 25 Balb/C mice divided into 5 groups including: the control, and treatment groups which given EEDA dose 0.31, 0.62, 1.24 g/kg and antihistamine drug. Treatment groups were induced the allergic model using Ovalbumin. On the 29th day, the mice were sacrificed and sera were processed with Elisa methods. The data were analyzed with Anova continued with Tukey test. The IgE level in EEDA 0.62 and 1.24 g/kg decreases with insignificantly difference with antihistamin drug. IL-4 level in EEDA is insignificant different. TNF-α levels in EEDA 1,24 g/kg increases with insignificantly difference with antihistamin drug. The conclusion is EEDA dose 0.62 and 1.24 g/kg is able to decrease the IgE level and EEDA dose 1,24 g/kg is able to increase TNF-α levels.